Ketamine: stimulating antidepressant treatment? - Malhi, G; Byrow, Y; Cassidy, F; Cipriani, A; Demyttenaere, K; Frye, M; Gitlin, M; Kennedy, S; Ketter, T; Lam, R; McShane, R; Mitchell, A; et al. (Cambridge University Press, 2016)
SUMMARY: The appeal of ketamine - in promptly ameliorating depressive symptoms even in those with non-response - has led to a dramatic increase in its off-label use. Initial promising results await robust corroboration and key questions remain, particularly concerning its long-term administration. It is, therefore, timely to review the opinions of mood disorder experts worldwide pertaining to ketamine's potential as an option for treating depression and provide a synthesis of perspectives - derived from evidence and clinical experience - and to consider strategies for future investigations. DECLARATION OF INTERESTS: G.S.M. Grant/research support: National Health Medical Research Council, NSW Health, Ramsay Health, American Foundation for Suicide Prevention, AstraZeneca, Eli Lilly & Co, Organon, Pfizer, Servier, and Wyeth; has been a speaker for Abbott, AstraZeneca, Eli Lilly & Co, Janssen Cilag, Lundbeck, Pfizer, Ranbaxy, Servier, and Wyeth; consultant: AstraZeneca, Eli Lilly & Co, Janssen Cilag, Lundbeck, and Servier. M.A.F. Grant support: AssureRx, Janssen Research & Development, Mayo Foundation, Myriad, National Institute of Alcohol Abuse and Alcoholism (NIAAA), National Institute of Mental Health (NIMH), Pfizer. Consultant (Mayo): Janssen Research & Development, LLC, Mitsubishi Tanabe Pharma Corporation, Myriad Genetics, Neuralstem Inc., Sunovion, Supernus Pharmaceuticals, Teva Pharmaceuticals. CME/travel support: American Physician Institute, CME Outfitters. Financial interest/Mayo Clinic 2016: AssureRx. S.H.K. Grant/research support: Brain Canada, Bristol Meyer Squibb, CIHR, Janssen, Johnson & Johnson, Lundbeck, Ontario Brain Institute, Pfizer, Servier, St. Jude Medical, Sunovion. T.A.K. Grant/research support (through Stanford University): Sunovion Pharmaceuticals and Merck & Co., Inc.; consultant/advisory board bember: Allergan, Inc., Janssen Pharmaceuticals, Myriad Genetic Laboratories, Inc., and Sunovion Pharmaceuticals; lecture honoraria (not Speaker's Bureau payments): GlaxoSmithKline, and Sunovion Pharmaceuticals; royalties from American Psychiatric Publishing, Inc. Also, AstraZeneca Pharmaceuticals LP provided publication support to Parexel for preparation of a manuscript. Spouse employee and stockholder of Janssen Pharmaceuticals. R.W.L. Honoraria for speaking/advising/consulting, and/or received research funds: AstraZeneca, Brain Canada, Bristol Myers Squibb, Canadian Institutes of Health Research, Canadian Depression Research and Intervention Network, Canadian Network for Mood and Anxiety Treatments, Canadian Psychiatric Association, Coast Capital Savings, Johnson and Johnson, Lundbeck, Lundbeck Institute, Pfizer, Servier, St. Jude Medical, Takeda University, Health Network Foundation, and Vancouver Coastal Health Research Institute. R.M. Investigator Janssen trials of esketamine; 'paid-for' ketamine clinic operated by Oxford Health NHS Foundation Trust - fees used to support the Trust. M.J.O. Consultant: Sunovion and Acadia Pharmaceuticals. Full-time employee of U.S. Department of Veterans Affairs. M.E.T. Advisory/Consultant: Alkermes, Allergan, AstraZeneca, Bristol-Myers Squibb Company, Cerecor inc., Eli Lilly & Co., Forest Laboratories, Gerson Lehrman Group, Fabre-Kramer Pharmaceuticals, Inc., GlaxoSmithKline, Guidepoint Global, H. Lundbeck A/S, MedAvante Inc., Merck and Co. Inc. (formerly Schering Plough and Organon), Moksha8, Naurex Inc., Neuronetics Inc., Novartis, Ortho-McNeil Pharmaceuticals (Johnson & Johnson; Janssen), Otsuka, Pamlab, L.L.C. (Nestle), Pfizer (formerly Wyeth Ayerst Pharmaceuticals), Shire US Inc., Sunovion Pharmaceuticals Inc., Trius Therapeutical Inc. and Takeda. Grant support: Agency for Healthcare Research and Quality, Alkermes, AssureRx, Avanir, Forest Pharmaceuticals, Janssen, National Institute of Mental Health, and Otsuka Pharmaceuticals. Speakers Bureau: None since June, 2010. Equity Holdings: MedAvante, Inc. Royalties: American Psychiatric Foundation, Guilford Publications, Herald House, W.W. Norton & Company, Inc. Spouse's employment: Peloton Advantage, which does business with Pfizer. M.T. Full-time employee at Lilly 1997 to 2008. Honoraria/consulted: Abbott, AstraZeneca, Bristol Myers Squibb, GlaxoSmithKline, Lilly, Johnson & Johnson, Allergan, Otsuka, Merck, Sunovion, Forest, Geodon Richter Plc, Roche, Elan, Alkermes, Lundbeck, Teva, Pamlab, Minerva, Wyeth and Wiley Publishing. Spouse was full time-employee at Lilly 1998-2013.